Electronic and magnetic properties of doped black phosphorene with concentration dependence - Wang, Ke; Wang, Hai; Zhang, Min; Liu, Yan; Zhao, Wei (Beilstein Journal of Nanotechnology, 2019)
In this paper, we employed first-principles calculations and chose Si and S atoms as impurities to explore the concentration-dependence of electronic structure and magnetism of doped phosphorene. It is found that the stability of doped phosphorene improves continuously with increasing the supercell size and decreasing impurity concentration due to the reduction of deformation. The stability of pristine phosphorene is invariable. The band structures of Si- and S-doped phosphorene without spin polarization always show metallic states suggesting the bandgap is insensitive to the in-plane size of the supercell and the dopant content. However, the results are fairly different once the spin polarization is taken into account. The band structures of Si- and S-doped phosphorene become those of a semimetal or a semiconductor as the in-plane size of the supercell goes up to 4 × 4 × 1 or 5 × 5 × 1 and the concentration goes down to 1.56% or 1%, respectively. In addition, we also observe that all Si- and S-doped phosphorene are magnetic, except for the Si-doped phosphorene with 2 × 2 × 1 supercell and a dopant content of 6.25%. The magnetic moment induced by 3p orbit–spin splitting increases with the in-plane size of the supercell, and the largest magnetic moment can be found in 4 × 4 × 1 and 5 × 5 × 1 supercells. These findings offer an alternative method to tune the magnetism and electronic structure of black phosphorene, which might be beneficial for its application in future spintronic devices.
Keywords: doped black phosphorene; electronic properties; first principles; magnetic properties